Analisis Siklus Perulangan Litologi pada Stratigrafi Formasi Sambipitu di Sungai Ngalang, Kecamatan Gedangsari, Kabupaten Gunung Kidul, DIY - flowers rizqi, Al Hussein Flowers (ReTII, 2019)
The Research area is located on Ngalang river, Gedangsari sub-district, Gunung Kidul Regency, Special Region of Yogyakarta. Physiographically and stratigraphically, research area is included in Southern Mountain Zone, composed by lithology of Sambipitu Calcareous Sandstone. Geomorphology of Ngalang River is controlled by geological structure, the results of this structural process in the form of Homoclinic plain which is the position of rocks relative to the south 20o. The intensive erosion process caused rocks exposed to the surfacel, one of the study area is in the village section of Ngalang in the Sambambitu formation. The depositional process phase in the Sambipitu Formation has a Uniqal pattern and relevance to previous lithology so it was interesting to examine the stratigraphic position and its lithological repetition pattern using the statistical method (Marcov Chain). This research was purpose to analyze the sedimentation pattern in the sambipitu formation, and it expected to be able to assist in predicting and interpreting the relevance of subsequent lithology appearances in each unit of lithologycle. The research method include making measured stratigraphy in the field. The results of the Markov chain analysis, lithology in the Sambipitu Formation has a non-random transition pattern. The results of statistical calculation show that the calculation value is greater than the Chi-square table value (333.9> 34.38) so that the Ho component is rejected Keywords:Ngalang River, Sambipitu, Marcov Chain, Sedimentation, Repetition Pattern